The study of intermetallic particles in aluminium alloy AA3104 can-body stock during homogenisation - Magidi, Livhuwani Tessa (Centre for Materials Engineering, 2018)
Aluminium alloy AA3104 is commonly used for the manufacture of beverage can bodies. This alloy has excellent formability and strength properties. The evolution of the AA3104 microstructure and intermetallic particles during thermo-mechanical processing (TMP) has a direct impact on quality parameters, which influence the formability of the material during beverage can deep drawing and wall ironing. These parameters are earing, tear-off and galling resistance. During homogenisation of AA3104 direct chill (DC) ingot, there is a phase transformation from β-Al₆(Fe,Mn) orthorhombic phase to the harder α-Alₓ(Fe,Mn)₃Si₂ cubic phase. Phase transformation occurs by diffusion of Si and Mn, where diffusion of Mn determines the rate of transformation. The presence of the α-phase intermetallic particles is crucial for galling resistance, thus improving the formability of the material. Ideal galling resistance requires 1- 3% total volume fraction (VF) of intermetallic particles, 50% of which should be the harder α- phase. The homogenisation treatment variables, such as temperature, as well as the effect of the intermetallic particle VFs with the correct β to α ratio is investigated. The aim of this research is to characterise intermetallic particles in the as-cast condition and investigate the evolution of particles as a result of a two-step homogenisation treatment, where the primary step temperature was varied between 560⁰C and 580⁰C, and the secondary step was performed at 520⁰C. The characterisation process involves particle phase identification using compositional and morphological analysis. A particle extraction setup is then used to extract intermetallic particles from the bulk specimen by dissolving Al matrix in dry butanol and those particles are analysed. The evolution of volume fraction of particles and their distribution is then investigated using light microscopy, image analysis, XRD and the Rietveld method. The SEM micrographs show a larger quantity of smaller, more closely dispersed intermetallic particles at the edge of the ingot, compared to those at the centre. The β-Al₆(Fe,Mn) phase is more geometric in shape, while the α-Alₓ(Fe,Mn)₃Si₂ phase comprises isolated areas of Almatrix within the particle centres (Chinese-script like). The phases are distinguished based on morphological identification using SEM and compositional identification using EDS, where Si content within the α-phase is used to differentiate between the phases. XRD patterns with the Rietveld method show the presence of β and α as the major phase particles within the homogenised specimens near the edge and at the centre. Phase quantification using 2-D analysis and particle extraction shows more α-phase near the edge and less α-phase at the centre. The two techniques agree in trend but differ in values. The particle extraction analysis is more trustworthy than 2-D particle analysis, where error is suggested to arise during thresholding in 2-D microstructural analysis. Additionally, homogenisation at 580°C/520°C yields more α-phase than homogenisation at 560°C/520°C both near the edge and at the centre of the ingot. Important observations emerge from this study: (i) Microstructural [two-dimensional (2-D)] and particle extraction [three-dimensional (3-D)] techniques agree when it comes to microstructural qualification and tend to slightly differ on particle quantification (value obtained from both techniques), (ii) both techniques show the presence of α and β phases, as well as reveal the morphological differences within the particles, (iii) both techniques show similar trends of high amount of β-phase during as-cast and an increase in α-phase after homogenisation due to phase transformation. Additionally, phase quantification reveals that more α-phase near the edge and less α-phase at the centre, and (iv) homogenisation at 560°C/520°C yields α-phase VF which is closer to the desired β→α ratio of 50% compared to homogenisation at 580°C/520°C. Therefore, homogenisation at 560°C/520°C is the better homogenisation treatment temperature option. Furthermore, both 2-D microstructural analysis and particle extraction analysis are reliable techniques that complement each other when qualitatively and quantitatively studying the evolution of intermetallic particles in aluminium alloy AA3104 canbody stock during homogenisation. However, particle extraction analysis has been shown to have a higher accuracy, thus is deemed more reliable.